External sulfate attack of cementitious materials: New insights gained through numerical modeling including dissolution/precipitation kinetics and surface complexation. (October 2017) - Soive, Anthony; Tran, Van Quan
Abstract: In this study, a new physically and chemically coupled model taking into account multiionic diffusion, precipitation/dissolution kinetics and surface complexation is proposed to predict the ingress of sulfate ions into saturated cementitious materials. The results are compared to experimental data and numerical profiles that were previously obtained on the total sulfate concentration profile in the material. The results show good agreement between experimental and numerical results. They also show that surface complexation has to be taken into account in order to reproduce the sulfate quantity peak experimentally observed. In addition, dissolution and precipitation kinetics are indispensable to retrieve the sulfate quantity amplitude and still more the slow decay of the sulfate quantity after the peak. Finally, the model may explain the supersaturation of the sulfate concentration with respect to ettringite because of the dissolution of monosulfoaluminate and ettringite precipitation kinetics. Moreover, it shows that the supersaturation increases with the concentration of the aggressive sulfate solution without significant increase in the total quantity of sulfate in the material. These results are coherent with the crystallization pressure theory.